2016
DOI: 10.7554/elife.17600
|View full text |Cite
|
Sign up to set email alerts
|

The proposed channel-enzyme transient receptor potential melastatin 2 does not possess ADP ribose hydrolase activity

Abstract: Transient Receptor Potential Melastatin 2 (TRPM2) is a Ca2+-permeable cation channel essential for immunocyte activation, insulin secretion, and postischemic cell death. TRPM2 is activated by ADP ribose (ADPR) binding to its C-terminal cytosolic NUDT9-homology (NUDT9H) domain, homologous to the soluble mitochondrial ADPR pyrophosphatase (ADPRase) NUDT9. Reported ADPR hydrolysis classified TRPM2 as a channel-enzyme, but insolubility of isolated NUDT9H hampered further investigations. Here we developed a soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 40 publications
1
69
0
Order By: Relevance
“…However, subsequent studies have since repudiated this mechanism, as the NUDT9H domain lacks enzymatic activity. Instead it has been suggested that the NUDT9H domain merely serves as a binding site for ADPR 20 .…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…However, subsequent studies have since repudiated this mechanism, as the NUDT9H domain lacks enzymatic activity. Instead it has been suggested that the NUDT9H domain merely serves as a binding site for ADPR 20 .…”
Section: Mainmentioning
confidence: 99%
“…Functional studies have shown that the interaction between the core subdomain of NUDT9H and the rest of the channel is important for stabilizing an open state of the TRPM2 channel, underscoring the importance of this secondary interface in channel opening 20 . Strikingly, our TRPM2 DR_Ca2+ structure adopts a combination of the two distinct interactions associated with the NUDT9H domain and the neighboring MHRs.…”
Section: Alternating Quaternary Structure Rearrangement In the Bottommentioning
confidence: 99%
“…Cyclic ADPR indirectly activates TRPM2 channels in a similar manner 55 . Interestingly, the NUDT9-H domain of TRPM2 channels has slow hydrolytic kinetics, thus it is likely involved in ADPR binding and channel gating, rather than ADPR hydrolysis 51, 56, 57 , as opposed to the homologous mitochondrial pyrophosphatase NUDIT9 57 . ADPR-induced gating of TRPM2 requires co-binding of Ca 2+ 58 , suggesting that the channel acts as a co-incidence detector of upstream signaling events involving increases in intracellular [Ca 2+ ] and generation of ADPR.…”
Section: Redox Regulation Of Trpm2mentioning
confidence: 99%
“…54 Cyclic ADPR indirectly activates TRPM2 channels in a similar manner. 55 Interestingly, the NUDT9-H domain of TRPM2 channels has slow hydrolytic kinetics; thus, it is likely involved in ADPR binding and channel gating, rather than ADPR hydrolysis, 51,56,57 as opposed to the homologous mitochondrial pyrophosphatase NUDIT9. 57 This study also linked TRPM2 activity to a reduction in transendothelial electrical resistance in cultured monolayers treated with H 2 O 2 , F I G U R E 2 Redox modifications of TRP channel activity.…”
Section: Redox Regulation Of Trpm2mentioning
confidence: 99%
“…For example, pyrophosphohydrolases are now known to cleave ADP‐ribose (yielding adenosine 5′‐monophosphate and ribose 5‐phosphate) . Recent studies indicate a broad swath of cellular roles for ADP‐ribose, including chromatin remodeling, membrane protein ion channel gating, and a host of processes dependent upon ADP‐ribosylation; this suggests that Nudix ADP‐ribose pyrophosphohydrolases may play roles in many physiological contexts. Other hydrolases are involved in eukaryotic and bacterial mRNA decapping by recognizing either the 5′‐7‐methylguanosine or the NAD mRNA cap, respectively, initiating the process of mRNA degradation .…”
Section: Introductionmentioning
confidence: 99%